1, 8‐diazabicyclo [5.4.0] undecano‐7‐ene functionalized ionic liquids for extractive desulfurization of fuels. Issue 3 (12th December 2022) - Zhao, Pingping; Wang, Xiaoxin; Wang, Qiang; Zhang, Lianzheng; Xu, Dongmei; Gao, Jun
Abstract: BACKGROUND: With strict regulations on environmental protection, the removal of sulfur compounds from fuels has become increasingly urgent by extraction desulfurization technology. RESULTS: A series of ionic liquid (IL) extractants for the removal of sulfides [benzothiophene (BT), thiophene (TH) and dibenzothiophene (DBT) in model oil] was developed. The ILs with functionalized 1, 8‐diazabicyclo [5.4.0] undecano‐7‐ene (DBU) cations and large volume difluoromethane sulfonimide (NTf2 ) anion as raw materials were synthesized. The performance of the ILs was characterized by Fourier transform infrared spectroscopy (FTIR), elemental analysis and nuclear magnetic hydrogen spectroscopy ( 1 H‐NMR) and other methods. Maximum removal efficiencies of 65.08% TH, 83.02% BT and 89.72% DBT were achieved in the presence of [CoDBU][NTf2 ] with functionalized carboxylation groups. In addition extractive desulfurization (EDS) was studied by tailoring the acid–base functional groups and viscosity of ILs. FTIR and the analysis of interaction energies were adopted to explore the interaction of ILs and sulfides. This indicated that the cooperative effects of hydrogen bonding, electrostatic interaction and π‐π interaction between sulfides and ILs were closely related to the high removal efficiencies of sulfides. CONCLUSIONS: The experimental results show that [CoDBU][NTf2 ] with functional carboxyl group is a clean and efficient extractant suitable for removing thiophene sulfides from model fuel oil. This work provides a reference process for the desulfurization of fuel oil in industry. © 2022 Society of Chemical Industry (SCI).